An Elite Roadway Illuminance Calculation (ERIC) Method Provides Optimum Performance and Cost-saving without Compromising Safety - Thurairajah, Uthayan (Recent Progress in Science and Technology Vol. 8, 2023)
This paper addresses the difficulties and consequences of the luminance calculation method for roadway lighting applications and recommends a novel illuminance calculation method as the best fit for Roadway Lighting Applications. This change would lower the costs of roadway lighting design while increasing safety, benefiting both society and the profession. Luminance calculations are complex, taking approximately five times as long as the new illuminance calculation method, providing no additional insight, and yielding the same design outcome. This paper conducts a comparative study and analyzes both methods using regular comparative analysis, quantitative and qualitative assessments, and offers a solution to the over-50-year-old challenge. The quantitative evaluation uses a sample case study and examines its corresponding benefit-cost ratio. The qualitative approach entails conducting a survey of peers and lighting designers. This is the first paper to address all of the parameters of roadway lighting in a comprehensive manner. This paper will be helpful for academics, researchers, scientists, engineers, consultants, architects, lighting designers, contractors, developers, financial institutions, and government agencies funding outdoor lighting.